Effect Of Video Encoding Scheme Of Battery Consumption Of Mobile Device - Mat Rawi, Nor Afifah; Muslim, Zulkiflee; Ayop, Zakiah; Nahar, Haniza; Mohd Abid, Mohd Asyadi 'Azam (Faculty Of Information And Communication Technology, UTeM, 2019)
Battery acts like a soul for mobile phones. It provides energy to the mobile phones. As long as the device is on, it will keep consuming the battery energy. Nevertheless, battery of mobile devices has limited power. In addition, the diversity of applications that are used reduce the battery lifetime. One of the application provided is a video player which mostly use for online streaming. However, the battery usage is difference while streaming a video. The codec used for video streaming affects the battery consumption. Therefore, the objective of this paper is to measure the battery consumption of mobile devices based on the type of video codec used. An empirical study was conducted by using a smartphone that supported by Samsung Galaxy Tab 2. The codec type such as WMV, MP4 and DIVX are among the codec, which be evaluated in this paper. In the end, the impact of several video codecs to the battery consumption are revealed. The outcome of this study assist the user to determine the best video codec for future use.